The influence of price earnings ratio on stock prices at PT Bank Central Asia Tbk period 2016 - 2021 - Janudin, Janudin; Warasto, Hestu Nugroho; Lestari, Indah (Journal of Economics and Business Letters, 2023)
This study investigates the impact of the Price-Earnings Ratio (P/E Ratio) on the stock prices of PT Bank Central Asia Tbk during the period from 2016 to 2021. Utilizing financial reports from PT Bank Central Asia Tbk, this research employs both descriptive and quantitative methods to explore the relationship. Descriptive statistics, alongside simple and multiple regression analyses, were conducted using SPSS version 25 to analyze the data. Contrary to common assumptions in financial analysis, the findings reveal that the P/E Ratio has an insignificant influence on the stock prices of PT Bank Central Asia Tbk within the timeframe studied.